Myanmar : Analysis of Farm Production Economics - World Bank Group (World Bank, Yangon, 2016)
This report was prepared by the World Bank in partnership with the Livelihoods and Food Security Multi-Donor Trust Fund (LIFT). Both the World Bank and the LIFT are actively involved in supporting Myanmar’s agriculture sector given its significance in poverty reduction and food security, and they both consider the lack of reliable farm data to be a significant constraint to designing effective programs and policies. This report fills some of the data gaps. In addition to presenting the collected data, the report offers the first analysis of these data. It focuses on the assessment of the extent of crop diversification and an analysis of farm production economics, in particular (partial factor) productivity of agricultural land and labor and crop profitability. This focus was chosen to study Myanmar’s commercial production areas and to facilitate international comparisons, as most international studies follow a similar approach, focusing on advanced farmers in commercial production areas. The four main findings of the report are as follows: (i) Myanmar’s farming systems are diversified and during the monsoon season most farms produce paddy, during the cool and dry seasons most farms produce crops other than paddy, mainly beans and pulses, oilseeds, and maize; (ii) the analysis reconfirmed that agricultural productivity in Myanmar is low, irrespective of what indicators are used, limiting the sector’s contribution to poverty reduction and shared prosperity; (iii) low productivity is a result of multiple factors, many of them associated with the undersupply of quality public services such as research, extension, and rural infrastructure, in delivery of which the government has a key role to play; and (iv) going forward and given that paddy is less profitable and more costly to produce than other crops in most agro-ecological zones, especially during the cool and dry seasons, it is desirable to redesign public programs from exclusive support of paddy production to support for broad-based agricultural development.